2001
DOI: 10.1159/000050465
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Charges Attributable to Bronchoscopy-Related Complications in Outpatients

Abstract: Background: Despite literature pertaining to algorithms of care, operating room charges and other financial management issues in medicine, there is a paucity of data pertaining to the fiscal consequences of bronchoscopic practice. Objective: To identify hospital charges directly attributable to bronchoscopy-related complications in outpatients. Methods: A prospective analysis of outpatient bronchoscopy-related complications, clinical outcomes and hospital charges resulting directly from procedure-related adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…The complication rates in our study are consistent with previously reported complication rates [9][10][11][12][13][14][15][16] . Overall complication rates from flexible bronchoscopy have been reported from 0.5 to 11% and serious complications from 0.8 to 5%, with mortality rates from 0 to 0.17% [10][11][12][13][14][15][16] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The complication rates in our study are consistent with previously reported complication rates [9][10][11][12][13][14][15][16] . Overall complication rates from flexible bronchoscopy have been reported from 0.5 to 11% and serious complications from 0.8 to 5%, with mortality rates from 0 to 0.17% [10][11][12][13][14][15][16] .…”
Section: Discussionsupporting
confidence: 92%
“…Overall complication rates from flexible bronchoscopy have been reported from 0.5 to 11% and serious complications from 0.8 to 5%, with mortality rates from 0 to 0.17% [10][11][12][13][14][15][16] . There were no deaths in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most patients with EBFI, bronchoscopic examination correlates with the radiographic findings. Bronchospasm, pneumothorax and bleeding are seen as complications in very small percentages (4.6, 0.4 and 0.7%, respectively) with flexible bronchoscopy [133]. In the literature, no additional risk related with EBFI was mentioned, either.…”
Section: Discussionmentioning
confidence: 99%
“…In such patients, CT scanning and fiber-optic bronchoscopy with bronchial wash, bronchoalveolar lavage fluid cytology and/or endobronchial, transbronchial biopsy play an important role [4,5,6]. It remains undetermined whether these procedures provide a cost-effective yield for the investigation of patients presenting with hemoptysis and negative chest radiograph [7, 8]. It has been suggested that the high diagnostic yield of bronchoscopy justifies its use for patients with a high risk of cancer, such as male cigarette smokers over 40 years old or for the evaluation of hemoptysis of more than 1 week’s duration [7].…”
Section: Introductionmentioning
confidence: 99%